Communicational Cosmopraxis of Brazil’s Kaiowa Indigenous People: Intermedial Resistance and the Struggle for Visibility - de Oliveira, Luciana (Intermédialités / Intermediality, 2021)
The struggles of Indigenous peoples in Brazil accumulate, among many other deficits, the absence in the fields of hegemonic visibility. The case of the Kaiowa and Guarani peoples deserves special attention, not only because it is the second largest Indigenous population in Brazil, but also because it is characterized as one of the most striking cases of necropolitical management by the State and private agents, in which peace takes on the face of an endless war. In the article, I present some of the creative ways of intermedial affirmation of existence developed by the Indigenous people in their struggle to retake their ancestral territory, as well as the attending fight for visibility, with repercussions on the means and meanings of what it is to resist.